2021
DOI: 10.1155/2021/1443996
|View full text |Cite
|
Sign up to set email alerts
|

Girder Longitudinal Movement and Its Factors of Suspension Bridge under Vehicle Load

Abstract: Vehicle load may not only cause vertical deformation and vibration of suspension bridge but also lead to longitudinal deformation and vibration. And the longitudinal behavior is closely related to the durability of the girder end devices and the bending fatigue failure of suspenders. In this study, the longitudinal deformation behavior and longitudinal vibration of suspension bridge under vehicles, as well as the related influencing factors, are investigated. The underlying mechanism of girder longitudinal mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The existing studies have shown that support friction also has a certain inhibitory effect on girder end displacement, and its effect cannot be ignored (Huang et al, 2021). In order to further obtain the influence of support friction resistance on the displacement of the That is, when the friction coefficient is within the range of 0~0.03, the increase of the friction coefficient has an obvious control effect on the main girder in the longitudinal displacement; While after the friction coefficient is greater than 0.03, the increase of the friction coefficient has little effect on the main girder in the longitudinal displacement, and the cumulative displacement of the girder end only fluctuates slightly, as shown in Table 5 In addition, it is observed that after the friction coefficient of the support is greater than 0.03, the displacement of the girder increased.…”
Section: Sensitivity Analysis Of Support Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing studies have shown that support friction also has a certain inhibitory effect on girder end displacement, and its effect cannot be ignored (Huang et al, 2021). In order to further obtain the influence of support friction resistance on the displacement of the That is, when the friction coefficient is within the range of 0~0.03, the increase of the friction coefficient has an obvious control effect on the main girder in the longitudinal displacement; While after the friction coefficient is greater than 0.03, the increase of the friction coefficient has little effect on the main girder in the longitudinal displacement, and the cumulative displacement of the girder end only fluctuates slightly, as shown in Table 5 In addition, it is observed that after the friction coefficient of the support is greater than 0.03, the displacement of the girder increased.…”
Section: Sensitivity Analysis Of Support Parametersmentioning
confidence: 99%
“…Current research shows that, in the bridge operation stage, the traffic load causes constant reciprocal movement of the longspan suspension bridge's main girder end, and the massive cumulative displacement will cause fatigue damage, insufficient durability, and other problems of the restraint devices such as expansion joints, dampers, and supports. In addition, the girder end displacement is also an important parameter for the design and selection of the key restraint device for the suspension bridge (Zribi et al, 2006;Huang et al, 2021). Therefore, it is of great necessity to study the longitudinal motion characteristics, influencing factors, and control methods of long-span suspension bridges' stiffened girders under traffic loads to ensure their safe operation.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the bridge deflection monitoring data mainly includes temperature-induced component, vehicle load-induced component, and test noise. [5][6][7] Effectively separating the components of temperature and vehicle load of deflection monitoring data is one of the important problems in bridge structure health monitoring. Most of the existing studies used filtering or time-frequency analysis methods.…”
Section: Correlation Model-based Decomposition Of Deflection Monitori...mentioning
confidence: 99%
“…[1][2][3][4] The analysis of monitoring data has revealed that vertical deflection of bridge structures is mainly induced by vehicle loads and environmental temperature. [5][6][7] The monitored deflection is found to correlate with site-specific vehicle loads and environmental temperature. The database collected by monitoring systems can be used to establish the correlation model of vehicle loads, temperature, and bridge deflection.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation